Transcriptomic and protein–protein interaction network analyses of the molecular mechanisms underlying the mycorrhizal interaction in Cypripedium macranthos var. rebunense - Jin, Chunyi; Kambara, Kota; Fujino, Kaien; Shimura, Hanako (Frontiers in Plant Science, 2025)
IntroductionOrchid mycorrhizal (OM) symbiosis plays an essential role in orchid seed germination and development, but its molecular mechanisms remain largely unexplored.MethodsTo comprehensively analyze gene expression associated with early fungal colonization, transcriptome analysis of Cypripedium macranthos var. rebunense was performed using mycorrhizal tissues prepared by inoculating seedling plants with a fungus that exhibited different mycorrhizal interaction properties among subcultures.ResultsColonization with the mycorrhizal fungus induced an increased expression of orchid genes encoding enzymes involved in cell wall synthesis, degradation, and modification, as well as those encoding transporters of sugars, amino acids, nucleic acids, and other nitrogen-containing compounds. Enrichment analysis focusing on genes associated with protein–protein interactions (PPI) suggested a potential role of lectin domain-containing receptor-like kinases (LecRLKs) in the recognition of fungal colonization and the induction of cell wall-modifying enzymes and nutrient transporters required for mycorrhizal formation. Kinase genes such as MAPKKK and serine/threonine protein kinase were upregulated in tissues exhibiting continued peloton formation, whereas these genes exhibited no changes in tissues showing no peloton formation four weeks after inoculation.DiscussionThese results suggest that the continuous phosphorylation signaling cascade plays a crucial role in the regulatory pathway for maintaining mycorrhizal interactions between Cypripedium and its mycorrhizal fungus.